Effect of Project-Based Learning Through Blended Learning on Website Design Skills - Dewi Sulistiyarini; Febrianto Sabirin; Dochi Ramadhani (Universitas Negeri Makassar, 2021)
This study aims to determine the website design skills of Information Technology and Computer Education Program (P.TIK) at IKIP PGRI Pontianak students and to determine the differences in website design skills of P.TIK students using Blended Learning (BL) and face-to-face learning (F2F) in website design project. The research method used in this study is an experimental method with a quasi-experimental form. The sample in this study amounted to 63 students who were divided into two groups namely classes that apply BL and classes that apply F2F in implementing website design projects. Data collection techniques in the form of measurement techniques using tools in the form of a portfolio. Data analysis techniques using descriptive statistics and inferential statistics. The results showed that the website design skills of students after working on a website design project were in the good category, and there were significant differences in website design skills between the groups applying BL and the groups applying F2F